Exploring Conversational Implicature Used by Teacher Through English Technology-Based Learning - Abdul Halim; Fitriyani; Rahmi Aulia Amir (International Journal of Language, Education, and Literature, 2025)
Conversational implicature is the meaning a sentence implies is different from its actual meaning. This study explores conversational implicature used by teacher through English Technology-Based Learning. This study aims to identify and classify the maxims are flouted through English Technology-Based learning, explain the functions of conversational implicature, and to find out teachers perceive about conversational implicature through English Technology-Based Learning process in Sd Telkom Makassar. This study uses data analysis. Qualitative methods are methods that aim to obtain descriptive data. The data in this study are conversational implicatures that transcribed into written text. Data were collected using selection, description and verification techniques. Data were analyzed using qualitative descriptive which is based on Sudaryanto's theory. The results of this study indicate that (1) there are four types of maxims that are flouted by teacher through English Technology-Based Learning process, there are maxim of quantity, maxims of quality, maxims of relevance, and maxim of manner. The most maxim flouted are maxim of quantity. (2) there are four functions of conversational implicature applied through English Technology-Based Learning. There are bald on record, positive politeness, negative politeness, and off-record. (3) the use of conversational implicature in the classroom plays an important role in building good relationships between teachers and students.